Visual search strategies of pedestrians with and without visual and cognitive impairments in a shared zone: A proof of concept study - Earl, Robyn; Falkmer, Torbjorn; Girdler, Sonya; Dahlman, J.; Rehnberg, A.; Falkmer, Marita (Pergamon, 2016)
© 2016 Elsevier Ltd. Shared zones have gained increasing popularity in urban land use and design as a means of incorporating the needs of multiple modes of transport, while at the same time promoting social interaction between users. Interactions within shared zones are based on a set of informal social protocols, communicated via eye contact and social cues. This proof of concept study utilised eye-tracking technology to examine the visual search strategies of individuals, with and without visual and cognitive impairments as they navigated a strategically chosen shared zone. In total 3960 fixations were analysed and the fixations were distributed across the shared zone and a pedestrian crossing. Those with impairments were more likely to fixate on traffic specific areas and objects compared to those without, suggesting that they required more input ascertaining when and where it was safe to perform tasks. However, the duration of fixation was not significantly different for an object whether it was traffic related or not, indicating a global need for increased processing time of the surrounding environment. Shared zones are claimed to increase driver awareness and safety and reduce congestion, but the implications on participation and safety for those with visual and cognitive impairments is yet to be extensively explored.